1989
DOI: 10.1149/1.2097097
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Etching in CrO3 ‐  HF  Solutions: II . Low Ratios

Abstract: The dissolution of silicon in CrO3‐HF solutions with a low false[HFfalse]/false[CrO3false] ratio was investigated by etching and electrochemical measurements. Etching is seriously inhibited in comparison to solutions with a high ratio. The electrochemical measurements showed that inhibition is caused by the formation of a mixed valence chromium complex which partly blocks the surface. It has been found that a reaction between intermediates of both the reduction and the oxidation processes plays an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A similar effect has been observed with silicon in HF solutions containing other oxidizing agents. 18,[20][21][22] Electrons from intermediates of the etching process can be thermally excited to the conduction band. Under depletion conditions, the electrons are driven from the surface, and registered as an anodic current.…”
Section: Resultsmentioning
confidence: 99%
“…A similar effect has been observed with silicon in HF solutions containing other oxidizing agents. 18,[20][21][22] Electrons from intermediates of the etching process can be thermally excited to the conduction band. Under depletion conditions, the electrons are driven from the surface, and registered as an anodic current.…”
Section: Resultsmentioning
confidence: 99%
“…7) The enhancement of the etching rate at defects was related to electron-hole recombination centers in the band gap of Si. [8][9][10] We previously reported that the hydrogenation of ELA poly-Si suppresses the etching at GBs, 11,12) which is attributed to the passivation of dangling bonds (DBs) by hydrogen. It was also found that a high density of active defects exists in grains.…”
Section: Introductionmentioning
confidence: 99%